The Relationship between Logistics Technology Innovation on Last Mile Delivery Operational Performance in Selangor, Malaysia. - Abdul Halim, Nur Sabrina; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2026)
The logistic sector, especially last-mile delivery, has been greatly influenced by Malaysia’s fast urbanization and e-commerce expansion. Last mile-delivery has changed from a support role to a crucial component of customer happiness and business success in heavily populated, commercialized areas like Selangor. High delivery costs, the need for quicker service, inefficient routes and rising customer expectations are just a few of the significant obstacles that logistics companies must overcome. Many logistics firms utilize logistics technological advancements like artificial intelligence (AI), GPS monitoring, automation and real time route optimization tools to overcome these obstacles and boost delivery effectiveness. The primary objectives include identifying the current levels of last-mile delivery operational performance and technology innovation in Selangor, and examining the relationship between technology innovation on last mile delivery operational performance. The research employed a quantitative approach, utilizing online questionnaires distributed to logistics companies in Selangor. A total of 182 responses were gathered from a target population of 759 logistics firms. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS), incorporating descriptive, reliability, normality, and Spearman correlation analyses. A pilot study involving 19 respondents was also undertaken to validate the survey instruments. The study found a significant positive relationship between technology innovation and last-mile delivery operational performance, with a Spearman's rho of 0.592 and a p-value of